'Cold spray +' as a new hybrid additive manufacturing technology: a literature review. (4th July 2019) - Li, Wenya; Cao, Congcong; Wang, Guoqing; Wang, Feifan; Xu, Yaxin; Yang, Xiawei
ABSTRACT: Cold spray (CS) is a new solid state coating technique that has attracted considerable attention as it is quite suitable for mass production of metallic materials or metal matrix composites. More recently, cold spray additive manufacturing (CSAM) has been proposed to fabricate/repair components or produce welding joint. However, inherently deficient in ductility/plasticity of CSAMed materials limits its application. Therefore, many hybrid processes have been proposed to further explore CS, which can be grouped together as 'cold spray +' hybrid processes (laser, shot peening and friction stir processing). This review will summarise the state-of-the-art of the 'cold spray +' processes to show their abilities and their effectiveness. Recommendations for further research and development have been incorporated to help widespread the process.